Akibat Hukum Perjanjian Jual Beli Tanah yang dilakukan Tidak di hadapan Pejabat Pembuat Akta Tanah (PPAT) - Fenesia Deni Batista; Retno Sariwati; Ariyanti Ariyanti (Bhirawa Law Journal, 2023)
One of the legal events that are often carried out by the community is entering into an agreement. According to the provisions in force, the land sale and purchase agreement must be made before the Land Deed Making Officer, however in daily life it turns out that there are still many transfers of land rights that are not made before the Land Deed Making Official. This will certainly be detrimental to the buyer, because he only controls the physical land rights. The research method used is empirical juridical. The results of this study indicate that the sale and purchase of land that is carried out not in the presence of the Land Deed Official is legal according to law as long as the material conditions are met. Settlements that can be made by the buyer, so that the land sale and purchase agreement made not in the presence of the Land Deed Official can have definite legal force by asking for a statement made or issued by the village head. The certificate is used as the basis for the implementation of the sale and purchase of land rights and has legal force if the implementation of the sale and purchase of land is known by the village head as a government official who controls the area concerned in remote rural areas.